Preparing The Art Of Writing In The Style Of Arabic Literature For Non-Arabic Speakers/ Ø¥Ø¹Ø¯Ø§Ø¯ ÙÙ† Ø§Ù„ÙƒØªØ§Ø¨Ø© Ø¨Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„Ø£Ø¯Ø¨ Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ù„ØºÙŠØ± Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Halimi, Halimi; Mustofa, Arif (Ijaz Arabi Journal of Arabic Learning, 2020)
The development of educational materials for the study of Arabic literature for Arabic speakers varies by teaching Arabic literature to non-Arabic speakers, if there is a curriculum and unique methods, because the first importance of studying Arabic literature in Arabic education programs for non-native speakers in the Arabic language department and literature The student's association with the Arabic language, the anchoring of its origins, and the enrichment of its linguistic balance, which ultimately leads to the student's empowerment, and to inform him in various aspects. The research was taught on the preparation of the art of the book in the manner of Arabic literature for non-Arabic speakers. This book has characteristics in other books. The results of this research relate to the characteristics of the said book: the researcher's analysis of the method, especially the poetry, the structure in one unit, or two successive units such as the atmosphere of emotion, emotion, style, rhythm, the basic idea, and subject matter. Thirdly, the researcher put in the target adequacy three objectives: communicative, methodological, and cognitive. The researcher integrates many subjects, from language and literature, from reality and fiction, theory and practice.